The Dragon queen. - Scholastic Inc. (London : Scholastic Children's Books, 2016)
"Emily Jones has been called back to the magical land of Elvendale--the elves need her help! an evil elf witch is trying to gain control, and has destroyed the trust between elves and dragons. Even worse, she has captured the dragon queen and one of her eggs! The elves have rescued her four other dragon eggs ... but they don't have long before the eggs hatch and need their mother. Emily and the elves must work together and overcome their fears to complete their mission. Can they save the dragons and defeat the witch before it's too late?"--Back cover.
4.0
3-6.
3-6
Keywords: Elves -- Juvenile fiction; Magic -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Elves -- Fiction; Magic -- Fiction -- Fiction; Quests (Expeditions) -- Fiction; Elves -- Fiction; Magic -- Fiction; Voyages and travels -- Fiction; Fantastic fiction